Socio-psychological factors, tax complexity, and turnover tax compliance: Evidence from SMEs in Kamukunji sub-county, Nairobi, Kenya - Muthoni, Beatrice Wairimu (Journal of Accounting, Business and Finance Research, 2025)
Taxation plays a pivotal role in sustainable development, and Kenya’s turnover tax (TOT) system was established to expand the tax base by targeting small and medium enterprises (SMEs). Despite this initiative, compliance levels remain below expectations. This study examined the influence of socio-psychological factors—tax awareness, tax morale, taxpayer egoism, and national pride—on turnover tax compliance among SMEs in Kamukunji Sub-County, Nairobi, with tax complexity as a moderating variable. An explanatory research design was adopted, targeting 3,217 registered SMEs. A stratified random sample of 356 enterprises was selected, and data were collected through structured questionnaires. Out of these, 271 valid responses were analyzed using descriptive statistics, correlation, and hierarchical multiple regression to test both direct and moderating effects. The results revealed that tax awareness, tax morale, and national pride had positive and significant effects on turnover tax compliance, while taxpayer egoism had a negative effect. Tax complexity significantly moderated these relationships by weakening the positive effects and amplifying the negative one. The model explained 53.8% of the variance in compliance (R² = 0.538), underscoring the importance of both intrinsic and contextual factors in influencing taxpayer behavior. The study concludes that compliance is not solely driven by enforcement but also by taxpayers’ moral orientation, civic responsibility, and perceptions of fairness. It recommends simplifying tax procedures, enhancing transparency, and integrating national pride into tax education programs to strengthen voluntary compliance and promote sustainable revenue mobilization.